Using learning styles as a basis for creating adaptive open learning environments: an evaluation. (2016) - Fasihuddin, Heba; Skinner, Geoff; Athauda, Rukshan
This paper presents an adaptive framework to personalise open learning environments. The design of the framework is grounded in cognitive science and learning principles. Theories of learning styles, specifically the model of Felder and Silverman (1988), have been considered and applied, with the technology of adaptive navigation support integrated into the design of an open learning environment, testing the use of sorting and hiding techniques. This adaptive framework adapts to learners' learning styles by sorting content based on learners' preferences and hiding the least preferred content. Detailed descriptions of the framework's functionalities and different components are presented in this paper. A prototype of this framework was developed and piloted on 88 undergraduate students. Subjective and objective data were collected and statistically analysed in order to evaluate the proposed framework and learners' satisfaction with the adaptive design of the open learning environment. The results and evaluations of this pilot study are reported in this paper, and these show that adapting to learning styles appears to be both helpful for learning and appreciated by learners.